Семантика тела в романе Артема Веселого «Гуляй Волга» - Мусий, Валентина Борисовна (Wydawnictwo Uniwersytetu Rzeszowskiego, 2024)
The object of the paper is Artem Vesely’s novel “Walk Volga” (1932) about the beginning of the colonization of Siberia by the Cossacks led by Yermak. The subject of the article is the place and role of descriptions of the body in the artistic world of the novel and in expressing the writer’s understanding of the historical nature of the Cossack campaign. Attention was paid to the form and external features of the body; to the body as a receptacle of energy, or, on the contrary, to that which is devoid of vitality; to the perception of someone else’s body; to the body as an object of external influences (natural conditions, labor, war) that deform the body. The author of the article comes to the conclusion that the images of the body and everything connected with it helped Artem Vesely express the idea of the ambiguous, antithetical character of Yermak’s campaign in Siberia.
Semantics of Body in the novel by Artem Vesely “Walk Volga”
Keywords: semantics; corporality; artistic world; style; author’s con- ception; colonization; Siberia; Artem Vesely